2021
DOI: 10.1101/2021.04.19.21255730
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The impact of COVID-19 on the oncologic outcomes of 3236 patients undergoing ColoRectal Cancer surgery in Northern Italy in 2019 and 2020 (COVID-CRC): results of a multicentric comparative cohort study

Abstract: Objective This study compared all patients undergoing surgery for colorectal cancer in 20 hospitals of Northern Italy in 2019 versus 2020, in order to evaluate whether COVID-19-related delays in the execution of colorectal cancer screening resulted in more advanced cancers at diagnosis and worse clinical outcomes. Design A retrospective multicentric cohort analysis of patients who underwent surgery for colorectal cancer in March-December 2019 (2019) versus March-December 2020 (2020). The independent predictors… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 26 publications
1
11
1
Order By: Relevance
“…When colorectal cancer surgery was performed during the COVID-19 pandemic, this did not increase the incidence of anastomotic leakage (OR, 0.71; 95% CI, 0.43, 1.16; p = 0.17; I 2 = 0%) ( Figure 3 ). The pooled effect sizes of the eight studies ( 1 , 21 , 22 , 24 , 25 , 27 , 28 ) showed no significant difference in mortality (OR, 1.27; 95% CI, 0.92, 1.75; p = 0.14; I 2 = 0%) ( Figure 4 ) between the two groups. Two studies ( 22 ) reported on ICU demand rate.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…When colorectal cancer surgery was performed during the COVID-19 pandemic, this did not increase the incidence of anastomotic leakage (OR, 0.71; 95% CI, 0.43, 1.16; p = 0.17; I 2 = 0%) ( Figure 3 ). The pooled effect sizes of the eight studies ( 1 , 21 , 22 , 24 , 25 , 27 , 28 ) showed no significant difference in mortality (OR, 1.27; 95% CI, 0.92, 1.75; p = 0.14; I 2 = 0%) ( Figure 4 ) between the two groups. Two studies ( 22 ) reported on ICU demand rate.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search yielded 1,349 potentially eligible records, of which 46 articles were reviewed in full. In addition to our study, 13 studies ( 1 , 12 , 21 31 ) published between 2020 and 2022 were included for analysis. The details of the 14 eligible studies are presented in Table 3 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations